Ejercicio de la autoridad y el poder político: ¿Cómo gobernar para generar confianza y esperanza en tiempos de crisis? - Sagasti, Francisco (Pontificia Universidad Católica del Perú, 2022)
In this article, the former President of the Republic of Peru, Francisco Sagasti, develops five points that he considers were the main features of the approach to the exercise of authority and political power within the Transition and Emergency Government that he led. These criteria were respect for the Constitution and the laws, honesty and transparency, teamwork and coordination, use of evidence and reliable information, search for the common good, and democratic leadership.

En el presente artículo, el expresidente de la República, Francisco Sagasti, desarrolla cinco puntos que él considera fueron los principales rasgos del enfoque que tuvo el ejercicio de la autoridad y del poder político durante el Gobierno de Transición y Emergencia que él dirigió. Dichos criterios fueron respeto a la Constitución y las leyes, honestidad y transparencia, trabajo en equipo y coordinación, uso de evidencia e información confiable, búsqueda del bien común, y liderazgo democrático.
Exercise of authority and political power: How to govern to build trust and hope in times of crisis?
Keywords: Autoridad; Poder político; Liderazgo político; Presidente; Gobierno de Transición y Emergencia; Perú; Authority; Political power; Political leadership; President; Transition and Emergency Government; Peru; https://purl.org/pe-repo/ocde/ford#5.05.00